Creating a Medication Therapy Observational Research Database from an Electronic Medical Record: Challenges and Data Curation - Rödle, Wolfgang; Prokosch, Hans-Ulrich; Neumann, Eva; Toni, Irmgard; Haering-Zahn, Julia; Neubert, Antje; Eberl, Sonja (Applied Clinical Informatics, 2024)
Background: Observational research has shown its potential to complement experimental research and clinical trials by secondary use of treatment data from hospital care processes. It can also be applied to better understand pediatric drug utilization for establishing safer drug therapy. Clinical documentation processes often limit data quality in pediatric medical records requiring data curation steps, which are mostly underestimated. Objectives: The objectives of this study were to transform and curate data from a departmental electronic medical record into an observational research database. We particularly aim at identifying data quality problems, illustrating reasons for such problems and describing the systematic data curation process established to create high-quality data for observational research. Methods: Data were extracted from an electronic medical record used by four wards of a German university children's hospital from April 2012 to June 2020. A four-step data preparation, mapping, and curation process was established. Data quality of the generated dataset was firstly assessed following an established 3 × 3 Data Quality Assessment guideline and secondly by comparing a sample subset of the database with an existing gold standard. Results: The generated dataset consists of 770,158 medication dispensations associated with 89,955 different drug exposures from 21,285 clinical encounters. A total of 6,840 different narrative drug therapy descriptions were mapped to 1,139 standard terms for drug exposures. Regarding the quality criterion correctness, the database was consistent and had overall a high agreement with our gold standard. Conclusion: Despite large amounts of freetext descriptions and contextual knowledge implicitly included in the electronic medical record, we were able to identify relevant data quality issues and to establish a semi-automated data curation process leading to a high-quality observational research database. Because of inconsistent dosage information in the original documentation this database is limited to a drug utilization database without detailed dosage information.
CRIS-Team Scopus Importer:2024-02-23
Keywords: data curation; Data Quality Assessment; electronic medical records; medication data; pediatrics

The epidemiology of drug-related hospital admissions in paediatrics – a systematic review - Eberl, Sonja; Heus, Pauline; Toni, Irmgard; Bachmat, Igor; Neubert, Antje (Archives of Public Health, 2024)
Background: Despite previous efforts, medication safety in paediatrics remains a major concern. To inform improvement strategies and further research especially in outpatient care, we systematically reviewed the literature on the frequency and nature of drug-related hospital admissions in children. Methods: Searches covered Embase, Medline, Web of Science, grey literature sources and relevant article citations. Studies reporting epidemiological data on paediatric drug-related hospital admissions published between 01/2000 and 01/2024 were eligible. Study identification, data extraction, and critical appraisal were conducted independently in duplicate using templates based on the ’Joanna Briggs Institute’ recommendations. Results: The review included data from 45 studies reporting > 24,000 hospitalisations for adverse drug events (ADEs) or adverse drug reactions (ADRs). Due to different reference groups, a total of 52 relative frequency values were provided. We stratified these results by study characteristics. As a percentage of inpatients, the highest frequency of drug-related hospitalisation was found with ‘intensive ADE monitoring’, ranging from 3.1% to 5.8% (5 values), whereas with ‘routine ADE monitoring’, it ranged from 0.2% to 1.0% (3 values). The relative frequencies of ‘ADR-related hospitalisations’ ranged from 0.2% to 6.9% for ‘intensive monitoring’ (23 values) and from 0.04% to 3.8% for ‘routine monitoring’ (8 values). Per emergency department visits, five relative frequency values ranged from 0.1% to 3.8% in studies with ‘intensive ADE monitoring’, while all other eight values were ≤ 0.1%. Heterogeneity prevented pooled estimates. Studies rarely reported on the nature of the problems, or studies with broader objectives lacked disaggregated data. Limited data indicated that one in three (median) drug-related admissions could have been prevented, especially by more attentive prescribing. Besides polypharmacy and oncological therapy, no other risk factors could be clearly identified. Insufficient information and a high risk of bias, especially in retrospective and routine observational studies, hampered the assessment. Conclusion: Given the high frequency of drug-related hospitalisations, medication safety in paediatrics needs to be further improved. As routine identification appears unreliable, clinical awareness needs to be raised. To gain more profound insights especially for generating improvement strategies, we have to address under-reporting and methodological issues in future research. Trial registration: PROSPERO (CRD42021296986)
CRIS-Team Scopus Importer:2024-09-06
Keywords: Adverse drug events; Adverse drug reactions; Children; Drug-related hospitalisations; Drug-related problems; Hospital admissions; Hospitalisation; Medication safety; Paediatric